PENENTUAN STATUS KEKERINGAN BERDASARKAN SUHU PERMUKAAN DAN INDEKS KELEMBABAN TANAH MENGGUNAKAN CITRA LANDSAT 8 DI KAPANEWON PAJANGAN KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Wasitama, Firdauzi; Virgawati, Sari (Universitas Pembangunan Nasional Veteran Yogyakarta, 2024)
Drought cases in Kapanewon Pajangan Bantul Regency often occur. The purpose of this study was to determine the level of soil moisture, land surface temperature conditions, and make a map of the distribution of drought status with a spatial approach to the Normalize Difference Moisture Index (NDMI), Land Surface Temperature (LST), and Normalize Difference Vegetation Index (NDVI) methods based on Landsat 8 imagery. The results showed that the soil moisture index was divided into 3 classes, namely humid with an area of 206,80 ha (6,27%), dry with an area of 2985,99 ha (90,53%), and very dry with an area of 105,649 ha (3,20%). The land surface temperature level is divided into 4 classes, namely very low (< 22,77 oC) with an area of 144,46 ha (4,38%), low (22,77 oC – 23,17 oC) with an area of 231,06 ha (7,31%), medium (23,17oC – 24,77oC) with an area of 2453,80 ha (74,37%), and high (> 24,77 oC) with an area of 460,15 ha (13,95%). The drought status in Kapanewon Pajangan is divided into 3 drought classes, namely low class with an area of 477,31 ha (14,55%), medium class with an area of 2589,98 ha (78,98%), and high class with an area of 212,15 ha (6,47%). The results of the Pearson correlation test of soil moisture index to water content at pF 2,54 and pF 4,2 included a strong positive correlation (r = 0,720 and r = 0,780). Pearson correlation test results of greenness level to water content at pF 2,54 had a moderately strong positive correlation (r = 0,598) and at pF 4,2 had a strong positive correlation (r = 0,783). Pearson correlation test results of LST soil surface temperature to moisture content at pF 2,54 had a strong negative correlation (r = -0,724) and at pF 4,2 had a very strong negative correlation (r = -0,838), while the correlation results with field soil surface temperature at pF 2,54 and pF 4,2 had a strong negative correlation (r = -0,631 and r = -0,787).